INKLUSIVITAS DALAM PENERIMAAN APARATUR SIPIL NEGARA (ASN) DI DISTRIK SOTA KABUPATEN MERAUKE: Implementasi Undang-Undang Nomor 8 Tahun 2016 Tentang Penyandang Disabilitas - Azis, Yuldiana Zesa; Rahail, Emiliana Bernadina (Astha Grafika, 2024)
The enactment of Law No. 8 of 2016 on Persons with Disabilities was driven by an urgent need to recognize and protect the rights of persons with disabilities in Indonesia. Prior to this law, persons with disabilities often faced discrimination and limited access in various aspects of life, including education, employment, healthcare, and community participation. The law reflects the Indonesian government's commitment to equality and inclusivity, aligning with the United Nations Convention on the Rights of Persons with Disabilities, ratified by Indonesia in 2011. This legislation aims to ensure that basic rights for persons with disabilities are protected, recognized, and respected, fostering a disability-friendly environment across sectors. Government efforts to promote equal opportunities include implementing inclusive civil servant (ASN) recruitment policies, particularly in Sota District, Merauke Regency, a remote border area with unique challenges and potentials. Inclusive ASN recruitment not only opens suitable employment opportunities for persons with disabilities but also raises awareness of accessibility needs, reduces social stigma, and sets an example for other institutions. Through qualitative research with a descriptive-analytical approach, this study explores the values, challenges, and opportunities surrounding the implementation of this law, assessing how inclusive policies affect community welfare and strengthen ties between government and society.